Implementing Industry 4.0 in SMEs Concepts, Examples and Applications - Matt, Dominik T.; Modrák, Vladimír; Zsifkovits, Helmut (Springer International Publishing : Imprint: Palgrave Macmillan, 2021)
This open access book addresses the practical challenges that Industry 4.0 presents for SMEs. While large companies are already responding to the changes resulting from the fourth industrial revolution , small businesses are in danger of falling behind due to the lack of examples, best practices and established methods and tools. Following on from the publication of the previous book 'Industry 4.0 for SMEs: Challenges, Opportunities and Requirements', the authors offer in this new book innovative results from research on smart manufacturing, smart logistics and managerial models for SMEs. Based on a large scale EU-funded research project involving seven academic institutions from three continents and a network of over fifty small and medium sized enterprises, the book reveals the methods and tools required to support the successful implementation of Industry 4.0 along with practical examples. Dominik T. Matt holds the Chair for Production Systems and Technologies and heads the research department "Industrial Engineering and Automation (IEA)" at the Faculty of Science and Technology at the Free University of Bozen-Bolzano (Italy). Further he is the Director of Fraunhofer Italia Research in Bolzano. His research focuses on Industry 4.0 and smart factories, the adoption of artificial intelligence in manufacturing as well as the digital transformation of industrial companies. Vladimír Modrák is Full Professor of Manufacturing Technology at Technical University of Kosice, Slovakia. He obtained his PhD at the same University in 1989. His research interests include cellular manufacturing design, mass customized manufacturing and planning/scheduling optimization. He is a Fellow of the European Academy for Industrial Management (AIM) since 2015. Helmut Zsifkovits is Professor of Industrial Logistics at Montanuniversitaet Leoben, Austria. He graduated from the University of Graz, Austria. His research interests include logistics systems engineering, supply chain strategy and operations management. He has teaching assignments at universities in Austria, Latvia, Colombia, and Germany, and professional experience in automotive industry, logistics consultancy and IT. In 2020, he was elected the president of the European Certification Board for Logistics (ECBL).